Holmium based nanoseconds pulsed fibre laser generation in the 2-micron region - Rahman, Mohd Fauzi Ab; Mahyuddin, Mohamad Badrol Hisyam; Latiff, Anas Abdul; Paul, Mukul Chandra; Dhar, Anirban; Das, Shyamal; Yupapin, Preecha Promphan; Yasin, Moh; Harun, Sulaiman Wadi (Elsevier, 2019)
We demonstrate and compare nanoseconds pulse induced by a Holmium oxide PVA film (HOPF, 50 μm thick) and a Holmium-doped fibre (HDF, 8 cm long) saturable absorber (SA) in a Thulium doped-fibre laser (TDFL) cavity. The HOPF SA produced a nanoseconds pulse operating at 1960 nm wavelength, with a pulse width of 57 ns. On the other hand, the HDF SA produced a pulsed laser operating at 1963 nm wavelength, with a pulse width of 53 ns. The HDF SA established a slightly better maximum pulse energy of 0.87 nJ as compared to the HOPF SA with only 0.62 nJ. © 2019 Elsevier GmbH